2019
DOI: 10.3389/fpsyt.2019.00078
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Symptoms in Schizophrenia Spectrum Disorders: A Systematic Review and Meta-Analysis

Abstract: Background: Recent studies have examined the association between autism spectrum disorder and schizophrenia spectrum disorders, describing a number of cognitive features common to both conditions (e.g., weak central coherence, difficulties in set-shifting, impairment in theory of mind). Several studies have reported high levels of autistic symptoms in population with schizophrenia spectrum disorders. Our study systematically reviews and quantitatively synthetizes the current evidence on the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 64 publications
2
74
1
Order By: Relevance
“…Our data showed that while AQ may represent a good instrument to detect autistic features among the general population (AUC = 0.84), it is not able to correctly discriminate between ASD and SSD (AUC = 0.63), with no significant differences either in the total score or in single subscales. Our results are in contrast with a recent meta-analysis [49] which found that patients in the SSD had lower autistic traits than ASD, but similar to the findings of Lugnegård et al [55], who reported no significant differences in self-reported AQ scores between autistic and psychotic patients while using the full AQ scales, and poor discriminant validity of the questionnaire (AUC = 0.65).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our data showed that while AQ may represent a good instrument to detect autistic features among the general population (AUC = 0.84), it is not able to correctly discriminate between ASD and SSD (AUC = 0.63), with no significant differences either in the total score or in single subscales. Our results are in contrast with a recent meta-analysis [49] which found that patients in the SSD had lower autistic traits than ASD, but similar to the findings of Lugnegård et al [55], who reported no significant differences in self-reported AQ scores between autistic and psychotic patients while using the full AQ scales, and poor discriminant validity of the questionnaire (AUC = 0.65).…”
Section: Discussionsupporting
confidence: 62%
“…Focusing on the differences in AQ scores between ASD and SSD, a recent meta-analysis has found that people with SSD have indeed significantly higher autistic traits than the general population and lower autistic symptoms than individuals with ASD [49]. However, other authors have reported that, even if AQ may represent a reliable screening tool in the general population, its usefulness in identifying ASD in clinical environments is questionable [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…ASD symptoms are more frequent in subjects diagnosed with SSD than in healthy controls (33,34), and appear to play a relevant role in the clinical situation of patients with SSD, as more severe ASD symptoms represent an individual predictor of worse SC performance (35,36) and poorer real-world social functioning (37), and are correlated with greater impairments in the ability to judge the quality of everyday functioning (38). Individuals diagnosed with SSD and showing prominent ASD features could represent a particular sub-population with specific clinical characteristics, including lower IQ and poorer cognitive performance (39,40) and worse response to antipsychotic treatment (41).…”
Section: Schizophrenia and Autism Spectra Disorders: Areas Of Clinicamentioning
confidence: 94%
“…Recent efforts have therefore focused more on dimensional rather than categorical approaches, under the assumption that both conditions represent extremes on a continuum of symptomatic severity, and that even isolated or low-intensity traits may affect clinical outcomes. Such studies have provided further evidence that autistic and psychotic traits co-occur at an elevated behavioral level in clinical samples (Barneveld et al, 2011;De Crescenzo et al, 2019;Esterberg, Trotman, Brasfield, Compton, & Walker, 2008;Fagel et al, 2013;Kincaid et al, 2017;Ziermans, Swaab, Stockmann, de Bruin, & van Rijn, 2017). From a cognitive and functional perspective, it is also well established that both ASD and PD are characterized by (partially) overlapping impairments compared to typical healthy comparisons, particularly in the social domain (Martinez et al, 2017;Pinkham et al, 2019;Sasson et al, 2007Sasson et al, , 2011Sasson et al, , 2016Velthorst et al, 2018).…”
Section: Introductionmentioning
confidence: 92%